2022
DOI: 10.55493/5003.v12i1.4449
|View full text |Cite
|
Sign up to set email alerts
|

Callus Induction of Fenugreek Trigonella Foenum-Graecum via Auxin Combined with Cytokinins Hormones, and Assessment of Toxicity via Brine Shrimp Assay

Abstract: Trigonella foenum-graecum (TFG) is a significant leguminous plant with diverse pharmacological effects. However, the resistant character of this plant accounts for significant difficulties in vitro multiplication, justifying the necessity to try new techniques for in vitro propagation of this plant. Hence, this study reports the effects of BAP, NAA, and 2,4-D on in vitro callus formation of seeds. The toxicity properties of seeds, plant, and callus aqueous extracts of TFG were measured by brine shrimp assay (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus it can be used effectively similarly to Kinetin. Agha et al (2022) evaluated the effects of BAP, NAA, and 2,4-D on vitro callus formation from fenugreek seeds. They achieved the highest amount of callus in the media containing both BAP and NAA combinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it can be used effectively similarly to Kinetin. Agha et al (2022) evaluated the effects of BAP, NAA, and 2,4-D on vitro callus formation from fenugreek seeds. They achieved the highest amount of callus in the media containing both BAP and NAA combinations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Agha et al (2022) findings with Fenugreek, though increasing concentrations of BAP increased shoot proliferation, the quality of plantlets was negatively affected ( Agha et al, 2022 ). These findings reinforce the general acceptance of its known function in micropropagation as the stimulant of the growth of axillary, adventitious, and foliar buds ( Pereira et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fenugreek originally came from the "Old World" Mediterranean region or portions of Asia. However, some have theorised that Turkey is its true origin [7][8][9]. Historically, fenugreek leaves and seeds were used for several therapeutic purposes, including treating mouth ulcers and chapped lips, treating baldness, and alleviating abdominal and abscess pain.…”
Section: Journal Of Asian Scientific Researchmentioning
confidence: 99%
“…Studies have indicated the plant contains rutin pigment, which has a significant role in protecting the heart and is neuroprotective and an anti-diabetic compound and works to protect the kidneys [35][36][37]. T. daniellii contain saponin, which is found in the fenugreek plant, and works as an antiinflammatory, hypocholesterolemic, and immunomodulatory [38][39][40]. A study conducted by Matsubara, et al [41];…”
Section: Characterisation Of Thaumatococcus Danielliimentioning
confidence: 99%